The red blood cell as a mediator of endothelial dysfunction in patients with familial hypercholesterolemia and dyslipidemia. (2nd November 2022) - Mahdi, Ali; Wodaje, Tigist; Kövamees, Oskar; Tengbom, John; Zhao, Allan; Jiao, Tong; Henricsson, Marcus; Yang, Jiangning; Zhou, Zhichao; Nieminen, Anni I.; Levin, Malin; Collado, Aida; et al.
Abstract: Background: Patients with familial hypercholesterolemia (FH) display high levels of low‐density lipoprotein cholesterol (LDL‐c), endothelial dysfunction, and increased risk of premature atherosclerosis. We have previously shown that red blood cells (RBCs) from patients with type 2 diabetes induce endothelial dysfunction through increased arginase 1 and reactive oxygen species (ROS). Objective: To test the hypothesis that RBCs from patients with FH (FH‐RBCs) and elevated LDL‐c induce endothelial dysfunction. Methods and results: FH‐RBCs and LDL‐c >5.0 mM induced endothelial dysfunction following 18‐h incubation with isolated aortic rings from healthy rats compared to FH‐RBCs and LDL‐c <2.5 mM or RBCs from healthy subjects (H‐RBCs). Inhibition of vascular but not RBC arginase attenuated the degree of endothelial dysfunction induced by FH‐RBCs and LDL‐c >5.0 mM. Furthermore, arginase 1 but not arginase 2 was elevated in the vasculature of aortic segments after incubation with FH‐RBCs and LDL‐c >5.0 mM. A superoxide scavenger, present throughout the 18‐h incubation, attenuated the degree of endothelial dysfunction induced by FH‐RBCs and LDL‐c >5.0 mM. ROS production was elevated in these RBCs in comparison with H‐RBCs. Scavenging of vascular ROS through various antioxidants also attenuated the degree of endothelial dysfunction induced by FH‐RBCs and LDL‐c >5.0 mM. This was corroborated by an increase in the lipid peroxidation product 4‐hydroxynonenal. Lipidomic analysis of RBC lysates did not reveal any significant changes across the groups. Conclusion: FH‐RBCs induce endothelial dysfunction dependent on LDL‐c levels via arginase 1 and ROS‐dependent mechanisms. Abstract :